2015
DOI: 10.1021/acs.jpcc.5b08692
|View full text |Cite
|
Sign up to set email alerts
|

The Performance Enhancement of Polymer Solar Cells by Introducing Cadmium-Free Quantum Dots

Abstract: The utilization of inorganic nanocrystals is one of the key strategies to improve the performance of polymer solar cells (PSCs). In this paper, CuInS2/ZnS (CIS-Z) quantum dots (QDs) were employed to improve efficiency of PSCs composed of poly [N-9″-hepta-decanyl-2,7-carbazolealt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′-ben-zothiadiazole)]­(PCDTBT)/fullerene derivative [6,6]-phenyl-C70-butyric acid methyl ester (PC71BM). The maximum power conversion efficiency of 7.19% was achieved, accounting for 21.6% enhancement com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Guo et al introduced CuInS 2 /ZnS QDs, which formed a unique energy level with the third component in a binary active layer with the PCDTBT donor and PC 71 BM acceptor, exhibiting improved charge generation and charge transport characteristics. In addition, they reported a PCE of 7.19%, which was an improvement of 21.6% compared to the existing PCE …”
Section: Introductionmentioning
confidence: 82%
“…Guo et al introduced CuInS 2 /ZnS QDs, which formed a unique energy level with the third component in a binary active layer with the PCDTBT donor and PC 71 BM acceptor, exhibiting improved charge generation and charge transport characteristics. In addition, they reported a PCE of 7.19%, which was an improvement of 21.6% compared to the existing PCE …”
Section: Introductionmentioning
confidence: 82%
“…It is worth emphasizing that the optimized addition of CsPbI 3 QDs (3 wt %) yields an enhancement in the PCE of 35 % relative to the control device, which is the highest increase reported amongst hybrid ternary devices (Supporting Information, Table S3), and more importantly, the efficiency of 10.84 % obtained with our champion device stands out among the highest for devices based on the light harvesting of a PTB7‐Th:PC 71 BM blend …”
Section: Resultsmentioning
confidence: 68%
“…To a considerably lesser extent, inorganic semiconductor nanoparticles or quantum dots (QDs) have also been explored as ternary components in BHJ OSCs. Initial reports demonstrated that the incorporation of well‐known semiconductor QDs such as colloidal CdSe or core–shell CuInS 2 /ZnS into conventional OSCs yielded rather modest amelioration of PCE. Overcoming the electrically insulating nature of the aliphatic capping ligands typically present in colloidally‐synthesized QDs via ligand engineering has advanced the performance of the standard inorganic QD additives, and in the last few years other nanoparticle additives (for example, ligand‐free C 3 N 4 QDs, black phosphorous QDs and antimonene quantum sheets) have also shown to improve the PCE of BHJ OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth emphasizing that the optimized addition of CsPbI 3 QDs (3 wt %) yields an enhancement in the PCE of 35 %r elative to the control device,w hich is the highest increase reported amongst hybrid ternary devices (Supporting Information, Table S3), [8,10,12,14] and more importantly,the efficiency of 10.84 %o btained with our champion device stands out among the highest for devices based on the light harvesting of aP TB7-Th:PC 71 BM blend. [43,44] Figure 2b shows the incident photon-to-current efficiency (IPCE) spectra obtained for the devices containing 0t o 3wt% (IPCE spectra for higher QD loading can be found in the Supporting Information, Figure S5), and the electron flow predicted from the IPCE and the AM 1.5 Gs tandard solar spectrum is included in Figure 2c.Asexpected, the values of IPCE increase in agreement with the observed enhancement in J sc ,albeit only within certain regions of the spectra.…”
Section: Research Articlesmentioning
confidence: 99%
“…To ac onsiderably lesser extent, inorganic semiconductor nanoparticles or quantum dots (QDs) have also been explored as ternary components in BHJ OSCs.I nitial reports demonstrated that the incorporation of well-known semiconductor QDs such as colloidal CdSe [11] or core-shell CuInS 2 /ZnS [12] into conventional OSCs yielded rather modest amelioration of PCE. Overcoming the electrically insulating nature of the aliphatic capping ligands typically present in colloidally-synthesized QDs via ligand engineering has advanced the performance of the standard inorganic QD additives, [13] and in the last few years other nanoparticle additives (for example,l igand-free C 3 N 4 QDs, [10] black phosphorous QDs [14] and antimonene quantum sheets [8] )have also shown to improve the PCE of BHJ OSCs.However,one class of emerging QDs (that is,t he inorganic lead halide perovskite QDs) have not yet been explored for use as ternary components in BHJ OSCs,d espite their excellent optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%